Analisis Unsur Intrinsik Dongeng Kancil dan Sahabat-Sahabatnya Sebagai Bahan Ajar Drama Kelas IV SD - Putri, Aldanisa Eka Iswantari; Widjojoko, Widjojoko; Wardana, Deni (Universitas Pendidikan Indonesia Kampus Serang, 2022)
Indonesian language learning is directed at students to be able to communicate effectively and efficiently, both orally and in writing. Indonesian language learning is also directed to appreciate literary works. Learning literature aims to introduce literary works as part of the richness of Indonesian culture to students. Literary works that are introduced to children are called children's literature. One of children's literature is fairy tales. Fairy tales are simple fantasy stories that are not really related and serve to convey moral teachings (educate) and entertain. The tale of the mouse deer is one of the familiar fairy tales and is a favorite reading for children. One of them is the story of Kancil and his Friends by Kak Thifa. This fairy tale has many moral messages in each story. From this fairy tale, the researcher will analyze the intrinsic elements contained in the fairy tale of Kancil and his friends, including: themes, characters, characterizations, settings, and messages. This research uses content analysis method, and uses a qualitative approach. The results of the intrinsic element analysis carried out by researchers on the fairy tale of Kancil and his friends can be obtained as teaching materials for drama in the fourth grade of elementary school.